2015
DOI: 10.1186/s40494-015-0066-x
|View full text |Cite
|
Sign up to set email alerts
|

Protecting silver cultural heritage objects with atomic layer deposited corrosion barriers

Abstract: Introduction: Silver, prized throughout history for its luster and shine, develops a black Ag 2 S tarnish layer that is aesthetically displeasing when exposed to atmospheric pollutants. Tarnishing, and subsequent polishing, leads to irreversible material loss and object damage. Currently, nitrocellulose coatings are often used to prevent silver from tarnishing, however non-uniform coatings and degradation over time limit their effectiveness. Atomic layer deposition (ALD) has been explored as a new method for c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…Moreover, the durability of the efficiency of these treatment is questioned. Concerning the specific case of silver, submitted to a tarnishing effect in several environment, some successful attempts were made by using nanotechnology to develop a nanometre scale protective layer (Marquardt et al 2015). For this metal, nitrocellulose treatments, manually applied are usually used.…”
Section: Nano Coatings Against Corrosionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the durability of the efficiency of these treatment is questioned. Concerning the specific case of silver, submitted to a tarnishing effect in several environment, some successful attempts were made by using nanotechnology to develop a nanometre scale protective layer (Marquardt et al 2015). For this metal, nitrocellulose treatments, manually applied are usually used.…”
Section: Nano Coatings Against Corrosionmentioning
confidence: 99%
“…For cultural heritage applications, the thickness of the coating layer must be sufficiently thick to be an effective diffusion barrier for corrosion processes and sufficiently thin to be Fig. 10 Different stages of ALD for an Al 2 O 3 coating (Marquardt et al 2015) optically transparent. Recent studies demonstrate that this optimal layer is about 20-100 nm (Paussa et al 2011;Marquardt et al 2015).…”
Section: Nano Coatings Against Corrosionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7][8][9] To establish adequate conservation treatments, it is fundamental to identify the corrosion products formed at the surface and to fully describe the corrosion mechanisms. Although there is signicant research in this area, the inuence of the constituent elements of the silver alloy on the corrosion mechanism is far away from being clearly identied.…”
Section: Introductionmentioning
confidence: 99%
“…ALD is a technique that was developed for use in microelectronics and allows for the buildup of an amorphous oxide film, one atom layer at a time. In previous work, our group has shown that ALD coatings can prevent tarnishing by acting as a diffusion barrier between silver objects and atmospheric corrosive species [4]. Benefits of this technique include atomic level uniformity of the coating regardless of object's topography, ease of removal using mild alkali solutions, and minimal impact on the object's appearance.…”
mentioning
confidence: 99%